2009
DOI: 10.1089/ees.2007.0272
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Optimization of Nitrogen Removal in a Full Scale Activated Sludge Plant

Abstract: This paper evaluates model-based upgrading of an activated sludge plant treating wastewaters of leather tanning industrial district with an average capacity of 13,000 m 3 /d. Significant impact of temperature changes on biochemical processes, such as nitrification and denitrification were quantified and used in setting the aeration control for process optimization in terms of total nitrogen removal. Model evaluation based upon kinetic and stoichiometric parameters specifically determined for the tannery wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
0
14
0
6
Order By: Relevance
“…The low organic nitrogen transformation is related to the results obtained by Insel et al [12] who determined that the limiting step in the removal of nitrogen in tannery effluent is the ammonification. They reported residual organic nitrogen concentration between 12 and 25 mg·L .…”
Section: Efficiency Of Cod Removalmentioning
confidence: 70%
See 3 more Smart Citations
“…The low organic nitrogen transformation is related to the results obtained by Insel et al [12] who determined that the limiting step in the removal of nitrogen in tannery effluent is the ammonification. They reported residual organic nitrogen concentration between 12 and 25 mg·L .…”
Section: Efficiency Of Cod Removalmentioning
confidence: 70%
“…This probably corresponds to recalcitrant or non-biodegradable nitrogen that could not be hydrolyzed [32]. In this regard, Boursier et al [33] and Insel et al [12] reported that the organic nitrogen present in industrial effluents from slaughterhouses and tanneries was in the particulate form of organic complex polymers and are probably not nitrificable, severely limiting the process of ammonification.…”
Section: Efficiency Of Cod Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…T hERE are more than 2,000 synthetic leather factories located in Southeast China, discharging off 10,000 thousands tons of wastewater per year, in which N,N-Dimethylformamide (DMF) was usually found, it was used for surface modification of PU (poly urethane) synthetic leather as a kind of solvent, and toxic and inhibitive to bacteria's activities [1,2,3]. Many kinds of physic-chemical or biological processes, such as Extraction, Sequencing Batch Reactor, Integrated Anoxic-aerobic Biochemical Process and etc, are applied to treat synthetic leather wastewater [4,5], and these experimental results shows that, some main water quality index parameters, such as CODCr (chemical oxygen demand), SS (suspended solid), Cr and sulfide in effluent, are usually measured with the National Wastewater Discharge Standard (NWDS), but the residual total nitrogen (TN) is hardly up to standard [6].…”
Section: Introductionmentioning
confidence: 99%